Crystal structure of 10-methoxy-7,11b,12,13-tetrahydro-6H-pyrazino [2′,3′:5,6]pyrazino[2,1-a]isoquinoline, C15H16N4O - Wang Zi Wei; Yu Yu (Zeitschrift für Kristallographie - New Crystal Structures)
C15H16N4O, monoclinic, P21/c (no. 14), a = 10.3021(8) Å, b = 15.7835(13) Å, c = 8.3052(7) Å, β = 90.894(7)∘ $90.894{\left(7\right)}^{° }$ , V = 1350.29(19)